2011
DOI: 10.1136/bjsm.2010.082545
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of physical activity–related injuries in Dutch children aged 10–12

Abstract: ISRCTN78846684.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 20 publications
2
46
0
1
Order By: Relevance
“…This is similar to other studies that found that lower body incurred more injuries than other regions during PE, leisure time, dancing and organized sports (Collard, Verhagen, van Mechelen, Heymans, & Chinapaw, 2011;Malkogeorgos et al, 2011). However, injuries sustained in judo competitions mostly involved the upper body (James & Pieter, 2003;Maciejewski & Pietkiewicz, 2016).…”
Section: Catherine Joy D Lariosa Dariusz Gozdowski Stefan Pietkiewsupporting
confidence: 92%
“…This is similar to other studies that found that lower body incurred more injuries than other regions during PE, leisure time, dancing and organized sports (Collard, Verhagen, van Mechelen, Heymans, & Chinapaw, 2011;Malkogeorgos et al, 2011). However, injuries sustained in judo competitions mostly involved the upper body (James & Pieter, 2003;Maciejewski & Pietkiewicz, 2016).…”
Section: Catherine Joy D Lariosa Dariusz Gozdowski Stefan Pietkiewsupporting
confidence: 92%
“…8 The costs for both of these sites (upper and lower extremity) were greater in the present study than in that of rugby league players that involved all ages and both sexes. However, injury sites were not corrected for the possible confounding effect of injury type -therefore we cannot exclude the possibility that the significantly higher average cost of fractures (Table 2) could have influenced the mean cost of injury sites in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…Medical treatments/services and the time that the injured player's parent/legal guardian were away from work were quantified using a cost diary used previously, 8 and which was adapted for use in South Africa. The South African version was adapted from the original version to provide a semi-structured guide for the telephonic interviewer to capture total quantity and type of medical service sought.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations